The effect of school starting age on academic performance in Hungary - Szilvia Hámori (Hungarian Academy of Sciences, Institute of Economics, 2007)
The study estimates the effect of school starting age on academic performance for Hungarian grade four students using the "Progress in International Reading Literacy Study" (PIRLS) and the "Trends in Mathematics and Science Study" (TIMMS). The study uses the control function approach, exploiting the exogenous variation in school starting age driven by the children's month of birth and the cut-off date regulation for enrolment. The results indicate a positive age effect on Reading, Mathematics and Science performance.
Keywords: I21; I28; J24; 330; Education; student test scores; enrolment age; identification; Schüler; Altersgruppe; Bildung; Bildungsertrag; Studium; Ungarn